Strategies for Incorporating Bilateral Training into a Virtual Environment - Merians, A.; Lewis, J.; Qinyin Qiu; Fluet, G.; Talati, B.; Adamovich, S. (2007 IEEE/ICME International Conference on Complex Medical Engineering, 2007)
We have previously designed a virtual reality-based training system for hand rehabilitation. Here we report the design of an extended version of the system that allows training of the hemiparetic arm and hand, and provides haptic assistance during hand and arm motions in three-dimensional space. It also allows bimanual training of the hand and arm. Hand training was based on a virtual piano activity that was designed to promote finger range of motion and independence of finger motion. Arm training was based upon unilateral and bilateral reaching to stationary and moving targets. The use of a three-dimensional robot based on admittance control allowed the use of active force applied by the subject as an input to the haptic controller. Two subjects post-stroke were trained for three weeks using computer game-like activities. Subjects improved on movement kinematics, kinetics and on several of the clinical tests.